The Impact of Social Vulnerability on Substance Use Detection Practices in Pregnancy - Lijewski, Virginia A.; Aldrich, Heather; Straub, Heather L. (American Journal of Perinatology, 2024)
This study aimed to synthesize current literature regarding the impact of social vulnerability on pregnancy-related substance use detection in the United States and highlight disparities in substance use detection practices. Clinicaltrials.gov, Google Scholar, PubMed (includes MEDLINE), and Cochrane Library databases were searched using the following Medical Subject Headings (MeSH): ([“pregnancy” or “prenatal”] AND [“substance use screening” or “urine toxicology testing” or “toxicology testing” or “urine drug screening” or “CRAFFT” or “4P's” or “4P's Plus” or “NIDA Quick Screen” or “DAST-10” or “SURP-P” or “WIDUS”], AND (“bias” or “disparities” or “social vulnerability”]). The search included systematic reviews, prospective and retrospective studies, randomized controlled trials, case studies, and qualitative and quantitative research from January 2014 through November 2023. Selected literature was limited to studies published in English, which included a study population of either pregnant individuals or pregnancy health care providers in the United States, and that were focused on inequities in pregnancy substance use detection. Using Covidence, three authors screened abstracts, and two screened full articles for inclusion. The included studies were evaluated for quality of evidence using the mixed methods appraisal tool. The search yielded 4,188 manuscripts; 37 were eligible for full review. A total of 18 manuscripts were included based on the relevancy of the topic. The most common social vulnerability domain identified was minority status (17/18), followed by socioeconomic status (11/18), household characteristics (8/18), and housing type (1/18). Social vulnerability plays a role in substance use detection among pregnant individuals. Most notably, race and ethnicity, age, and public insurance lead to increased rates of detection, though most individual factors need to be studied in greater depth. This study was registered with PROSPERO (PROSPERO ID CRD42022352598), the International Prospective Register of Systematic Reviews.Key Points
Keywords: substance use detection; urine toxicology testing; health disparities; social vulnerability; pregnancy